"People's Heads Do Not Even Go There": Public Perceptions to Transracial Familial Intimacy. Issue 1 (2nd January 2018) - Goss, Devon R.
ABSTRACT: U.S. culture uses phenotypical resemblance as the primary way that family ties are legitimized and authenticated. Transracial adoption challenges this type of kinship authentication because of the lack of resemblance among family members. This article explores how transracial family members experience and perceive interactions and conversations regarding family acknowledgment, belonging, and resemblance. This study finds that transracial family members must contend with being both hypervisible and incomprehensible as a family formation due to normative assumptions of which family members "belong" together. Transracial family members use specific strategies to challenge and reinforce these assumptions. To examine this phenomenon, 30 in-depth, life-story interviews with transracial family members are employed.